2018
DOI: 10.1038/s41417-018-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumour effects of rapamycin and oncolytic reovirus

Abstract: There are currently numerous oncolytic viruses undergoing clinical trial evaluation in cancer patients and one agent, Talimogene laherparepvec, has been approved for the treatment of malignant melanoma. This progress highlights the huge clinical potential of this treatment modality, and the focus is now combining these agents with conventional anticancer treatments or agents that enhance viral replication, and thereby oncolysis, in the tumour microenvironment. We evaluated the combination of reovirus with rapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This was presumably due to the induction of autophagic cell death [87,88]. Increased efficacy through modulation of autophagy in similar settings is also described for other OVs [75,76]. The hyperactivation of AKT during mTORC1 inhibition might have benefits when combined with myxoma virus [81][82][83], but in other settings can have a negative effect on survival.…”
Section: Pi3k/akt/mtor Pathway Antagonistsmentioning
confidence: 72%
See 1 more Smart Citation
“…This was presumably due to the induction of autophagic cell death [87,88]. Increased efficacy through modulation of autophagy in similar settings is also described for other OVs [75,76]. The hyperactivation of AKT during mTORC1 inhibition might have benefits when combined with myxoma virus [81][82][83], but in other settings can have a negative effect on survival.…”
Section: Pi3k/akt/mtor Pathway Antagonistsmentioning
confidence: 72%
“…Combining rapamycin with the highly IFN-sensitive VSV-mutant strain (VSVΔM51) led to significant increase of the oncolytic effect [ 74 ]. In addition other oncolytic RNA viruses, such as NDV and reovirus, showed improved oncolytic effect in mice when co-treated with rapamycin [ 75 , 76 ]. Oncolytic DNA viruses also benefit from co-treatment with rapamycin.…”
Section: Combinations Affecting Viral Propagation In Tumor Cellsmentioning
confidence: 99%
“…Further research should be undertaken to improve some aspects of reovirus therapy, such as the safety and delivery methods. As multiple ways of treating cancers have become an exciting prospect, a combination of reovirus with chemotherapeutic drugs has shown significant potential advantages, and it is reported that an agent of treating malignant melanoma, rapamycin which combined with reovirus can improve the anti-tumor efficacy, 23 and a combination of reovirus and the immune checkpoint blockade also seems to be a powerful immunotherapy of treating breast cancer. 24 In our study, the ARV showed the significant viral infectivity and efficacy of its oncolytic activity, along with a clear safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…The current emphasis is on combining these viruses with molecules that upregulate viral replication, thus increasing oncolysis. Based on potential mechanisms by which mTOR inhibitors might enhance viral oncolysis, the antitumor effects of the combination of rapamycin and reovirus was tested in B16F10 cell, a murine model of malignant melanoma, providing evidence of synergistic antitumor cytotoxicity [159].…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%